Effects of food and race on the pharmacokinetics of lazertinib in healthy subjects and patients with EGFR mutation-positive advanced non-small cell lung cancer. (January 2023) - Huh, Ki Young; Lim, Yeji; Yoon, Deok Yong; Hwang, Jun Gi; Sim, Sujin; Kang, Jiah; Wang, Jangyoung; Kim, Mikyung; Jang, Seong Bok; Shreeve, S. Martin; Mehta, Jaydeep; Haddish-Berhane, Nahor; et al.
Highlights: The systemic exposure of lazertinib was not significantly altered by food. Lazertinib can be administered without regard to food, enhancing the patient's adherence to treatment. Non-Asian and Asian patients showed similar systemic exposure both after single and multiple doses of lazertinib. No separate dose adjustment of lazertinib for race is required. Abstract: Objectives: Lazertinib is a potent, irreversible, brain-penetrant, mutant-selective, and wild type-sparing third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor indicated for advanced non-small cell lung cancer (NSCLC). The study aimed to evaluate the effects of food and race on the pharmacokinetics (PK) of lazertinib from a healthy volunteer trial and PK data from NSCLC patients with EGFR mutation. Materials and methods: An open-label, single-dose, two-period, single-sequence crossover study was conducted in healthy subjects with two race groups (non-Asian and Asian). Subjects orally received a single dose of lazertinib 240 mg in fasted and fed state (high-fat meal) in each period separated by a 21-day washout. An open-label, multicenter, phase 1/2 study was conducted in Asian and non-Asian patients with NSCLC. Patients were given oral lazertinib 20–320 mg once daily in fasted state continuously in 21-day cycles. PK parameters were evaluated using non-compartmental analysis. Results: A total of 24 healthy subjects (12 non-Asians and 12 Asians) and 52 NSCLC patients (22 non-Asians and 30 Asians) were evaluated. The change in the overall systemic exposure of lazertinib at fed state was less than 15%. Non-Asians showed 58–76% of the systemic exposure than Asians in healthy subjects. In contrast, there were no significant differences in systemic exposure by race both after single and multiple doses among NSCLC patients. Conclusion: Lazertinib can be taken with or without food considering the comparable systemic exposures related to food. Although effect of race was not consistent across studies, there was no evidence for dose adjustment based on race.